Penguatan Pendidikan Agama Islam Di TK Tunas Mekar melalui Metode Storytelling - Sitto Rahmana (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This activity is about strengthening Islamic religious education in Tunas Mekar Kindergarten through the storytelling method. The method of strengthening is through stories of the Prophet and Apostles and the Qur'an. This method utilizes children's imagination, making learning more interesting and easy to understand. The purpose of strengthening Islamic religious education in early childhood is very important to form a solid foundation in the moral, spiritual, and social development of children. In addition, strengthening Islamic religious education in early childhood aims to form a strong character, have strong faith, and live a life full of values ​​of goodness, peace, and balance. Through the introduction of Islamic teachings from an early age, children are taught to behave in accordance with religious guidance, such as speaking politely, respecting parents, acting honestly, and caring for others. The implementation method used is the storytelling method with an educational audio and video approach. Based on the results of the counseling, it shows that the storytelling method is an effective way to teach Islamic religious values ​​to children. By using stories from the Qur'an, hadith, stories of prophets, companions, or noble morals, children can understand religious teachings in a fun and easy-to-digest way. In addition, this learning can also improve children's social and emotional skills and form good character from an early age.